Pengaruh Growth Opportunity, Net Working Capital dan Firm Size Terhadap Cash Holding - Riyadi, Wulan; Ginanjar, Yogi; Indriyani, Indriyani (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2025)
Cash holding is an important aspect in corporate financial management, which includes cash for operational needs, investment, dividend distribution, and dealing with unexpected situations. Each company has a different policy in managing and maintaining cash supplies. This is due to differences in characteristics and conditions faced by companies as well as different motivations in holding cash. The purpose of this study is to ascertain how cash holdings are impacted by growth opportunity, net working capital, and business size. The research method used is a quantitative method with a descriptive and verification analysis approach. The population of this study consisted of 92 property and real estate sector companies listed on the Indonesia Stock Exchange in 2021-2023. The method of sampling was non-probability sampling with a purposive sampling method, which resulted in 30 companies as samples with an observation period of 3 years. Data analysis was carried out using panel data regression using Eviews 13 software. The results of the study show that partially growth opportunity, net working capital and firm size have a significant effect on cash holding. Keywords: Growth Opportunity, Net Working Capital, Firm Size, Cash Holding